Pengaruh Work Family Conflict, Work Life Balance , Dan Beban Kerja Terhadap Kinerja Pegawai Dinas Perindustrian Dan Perdagangan Provinsi Kepulauan Riau Melalui Komitmen Kerja Sebagai Variabel Intervening - Nasution, Novita; E Rumengan, Angelina; Puspita Dewi, Nolla (Bahtera Inovasi, 2025)
Imbalance between work and family is a variable that impacts employee performance, as it can negatively impact both family and performance. If one role at work requires more effort or attention than the role at home, work-family conflict will arise. The majority of employees are married. This indirectly reduces the amount of time spent together with their families. The research approach used a quantitative approach, as this research is presented numerically. Work-life balance and work-family conflict have no significant effect on work commitment, while workload has been shown to increase employee commitment. All of these variables—work-life balance, work-family conflict, workload, and work commitment—have a positive effect on employee performance. However, work commitment does not act as a significant mediator in the relationship between work-life balance, work-family conflict, or workload and performance, so the influence of these variables on performance is direct.